VD_FINDINFO Jug / 2021 / 235 vom 2. Juli 2020 - VD Tribunal cantonal (2020)
FIXATION DE LA PEINE, SURSIS À L'EXÉCUTION DE LA PEINE, JEUNE ADULTE, MESUREDROIT PÉNAL | 19 al. 2 CP, 42 al. 1 CP, 47 CP, 48 let. c CP, 61 CP